Molecular Autism - Baron-Cohen, Simon; Buxbaum, Joseph
Molecular Autism is a peer-reviewed, open access journal that publishes high-quality basic, translational and clinical research that has relevance to the etiology, pathobiology, or treatment of autism and related neurodevelopmental conditions. Research that includes integration across levels is encouraged. Molecular Autism publishes empirical studies, reviews, and brief communications. We encourage submissions from a range of fields including (but not restricted to) genetics, molecular neurobiology, neuropathology, neuroimaging, cognitive neuroscience, epidemiology, and biomarker discovery. Molecular Autism also publishes articles on screening, diagnosis and classification, including articles that consider subgrouping to refine our understanding of basic mechanisms. Intervention studies are also welcome, especially when considered with respect to revealing causal mechanisms. Although the primary focus is on conditions on the autism spectrum (including Asperger syndrome), the scope encompasses molecular research into related neurodevelopmental conditions such as specific language impairment, dyspraxia, and specific or general developmental delays; and into related medical syndromes such as fragile X syndrome, tuberous sclerosis, and Rett syndrome. Molecular Autism also considers articles with no molecular data but which, in the long-term, may close the gap from molecule to behavior in autism. The journal welcomes reports and reviews of good science that proceed from either end of this complex chain of events: from molecule upwards, or from behavior downwards. Reports and reviews can be basic and/or translational.